Current concepts in the pathogenesis of spondyloarthritis - Nibha Jain; Arumugam Moorthy (Indian Journal of Rheumatology)
Pathogenesis of spondyloarthritis (SpA) is multifactorial and still not understood entirely. The role of genetics including human leukocyte antigen B27 has been investigated extensively, which along with genome-wide association studies has helped us understand and postulate various theories. Environmental factors including gut dysbiosis, mechanical stress, and transduction have been implicated in the pathogenesis. Recently, the interleukin (IL)-17/IL-23 pathway has been major focus due to it being therapeutic target. Herein, we reviewed various recent developments and current concepts in the pathogenesis of SpA.